Focal Dystonia in Musicians: Phenomenology and Musical Triggering Factors [Distonía del Músico: Fenomenología y Desencadenantes Vinculados a la Ejecución Musical] - Chana-Cuevas, P (Spanish Society of Neurology, 2015)
Dystonias are defined as a joint sustained and involuntary contraction of agonist and antagonist muscles, which can cause torsion, repetitive abnormal involuntary movements, and/or abnormal postures. One special group of dystonias are those known as occupational, which include dystonia disorders triggered by a repetitive motor activity associated with a specific professional activity or task. Musicians are a population particularly vulnerable to these types of dystonia, which are presented as a loss of coordination and voluntary motor control movements highly trained in musical interpretation. Our aim is to describe a clinical series of focal dystonias in musicians evaluated and treated in our centre. Patients and methods: Data is presented on a clinical series of 12 musicians with occupational dystonia. Their history and phenomenology are described, as well as well as their outcome after therapy. Results: Demographic details: Mean age 34.8 ± 11.8 years, 10 males (83.3%) and 2 females (16.7%). Clinical history: History of trauma in dystonic segment, 6 patients (50%); family history of neurological diseases in first-degree relatives, 6 patients (50%); occupational history according to music category, 8 patients (66.6%) were classical musicians and 4 patients (33.3%) were popular musicians. Phenomenology: The dystonia syndrome was characterised by having a mean age of onset of 28.2 ± 11.3 years (range 18-57 years). The segment affected was the hand (91.7%) in 11patients. Of all the musicians seen in the clinic, 9 of them (75%) received therapy. The majority of patients appeared to have triggering factors specific to musical execution and linked to the requirement of fine motor control. It should be mentioned that 50% of the musicians treated maintained their professional activity or position in the orchestra to which they belonged. Conclusions: The majority of our phenomenological findings are consistent with those reported in the current literature. However, it is worth mentioning the presence of triggering factors attributed to the specific requirements of performing music, linked to the participation of fine motor control. © 2013 Sociedad Española de Neurología.